Alpha B‐crystallin promotes the invasion and metastasis of gastric cancer via NF‐κB‐induced epithelial‐mesenchymal transition - Chen, Dehu (J Cell Mol Med, 2018)
Alpha B‐crystallin (CRYAB) is overexpressed in a variety of cancers. However, little is known about its specific function and regulatory mechanism in gastric cancer. Here, we first explore the role of CRYAB in gastric cancer progression and metastasis. The expression of CRYAB was determined by western blot and immunohistochemistry in gastric cancer tissues. Besides, methods including stably transfected against CRYAB into gastric cancer cells, western blot, migration and invasion assays in vitro and metastasis assay in vivo were also conducted. The expression of CRYAB is up‐regulated in gastric cancer tissues compared with matched normal tissues. High expression level of CRYAB is closely correlated with cancer metastasis and shorter survival time in patients with gastric cancer. Additionally, CRYAB silencing significantly suppresses epithelial‐mesenchymal transition (EMT), migration and invasion of gastric cancer cells in vitro and in vivo, whereas CRYAB overexpression dramatically reverses these events. Mechanically, CRYAB facilitates gastric cancer cells invasion and metastasis via nuclear factor‐κ‐gene binding (NF‐κB)‐regulated EMT. These findings suggest that CRYAB expression predicts a poor prognosis in patients with gastric cancer. Besides, CRYAB contributes to gastric cancer cells migration and invasion via EMT, mediated by the NF‐κB signalling pathway, thus possibly providing a novel therapeutic target for gastric cancer.